Impact of macroeconomic risk factors, adoption of financial derivatives and corporate tax avoidance on working capital management, and firm performance - Mohammad Reyad, Hossain (2022)
Working capital management (WCM) has attracted increasing attention from businesses due to its sensitivity toward a firm’s financial efficiency and health. In any business, managing working capital (WC) is a never-ending task, and a constant inflow of funds needs to be ensured to keep the daily operations of the firm motoring along smoothly. To achieve this, firms need to understand which factors affect the investment of working capital. Macroeconomic risk factors draw major attention from businesses due to the inherent risk involved in working capital components, notably for firms in the United States, the United Kingdom, Germany, and China that are heavily involved in international trade. Therefore, the primary objective of this study is to examine the effect of macroeconomic risk factors on WCM. Subsequently, this study examines how the interaction between financial derivatives, corporate tax avoidance (CTA), and WCM influences the firms' performance amid volatility in macroeconomic risk factors. This research examines non-financial firms from 2006 to 2020, including 7645 firms from the USA, 1107 firms from the UK, 683 firms from Germany, and 4403 firms from China. The regression analysis begins with Ordinary Least Squares regression (OLS) to analyze the research objectives. However, Durbin–Wu–Hausman test indicates that endogeneity is a major issue in this study's OLS model. Hence, the two-step system Generalized method of moments (GMM) estimation technique is employed to examine the research objectives. This study finds that economic policy uncertainty (EPU) has a significantly negative relationship with CCC for firms in the USA, Germany, and China but a positive relationship for UK firms. On the other hand, foreign exchange risk (FX risk) has a significantly positive effect on CCC for firms in the USA, the UK, and China but a negative effect for firms in Germany. Furthermore, the current study reveals a positive association between the interaction of CCC and CDS on the ROA of all the countries' firms. This may be related to CDS adoption enhancing firms' WC financing, allowing them to maintain a higher CCC level. The adoption of CDS may drive firms to invest more in WC to dominate sales and grab market potential. Therefore, higher investment in WC yields a firm to have a higher ROA. Similarly, the current research discovers a positive effect of the interaction between CCC and CTA on ROA for all the sample countries' firms. As a kind of operational hedging, tax avoidance may insulate businesses from cash flow uncertainties during increased macroeconomic volatility. Firms may conserve the tax money for better WC management, greater WC investment to boost sales, and a better ROA. Nonetheless, this research sheds light on the literature demonstrating that firms may increase WC investment to achieve higher profitability when CDS and CTA are present to handle WC financing constraints. The study's most important implication is that financial derivatives should be widely used during periods of macroeconomic instability. Businesses need government-enforced laws to help them avoid paying taxes. As a result, businesses are resilient even under harsh economic conditions.